Emergence of dengue virus type 4 genotype IIA in Malaysia - AbuBakar, Sazaly; Wong, P.F.; Chan, Yoke Fun (2002)
Phylogenetic analyses of the envelope (E) gene sequence of five recently isolated dengue virus type 4 (DENV-4) suggested the emergence of a distinct geographical and temporal DENV-4 subgenotype IIA in Malaysia. Four of the isolates had direct ancestral lineage with DENV-4 Indonesia 1973 and showed evidence of intra-serotypic recombination with the other recently isolated DENV-4, MY01-22713. The E gene of isolate MY01-22713 had strong evidence of an earlier recombination involving DENV-4 genotype II Indonesia 1976 and genotype I Malaysia 1969. These results suggest that intra-serotypic recombination amongst DENV-4 from independent ancestral lineages may have contributed to the emergence of DENV-4 subgenotype IIA in Malaysia.